Comparing effects of insulin analogues and human insulin on nocturnal glycaemia in hypoglycaemia‐prone people with Type 1 diabetes. Issue 5 (14th February 2017) - Kristensen, P. L.; Tarnow, L.; Bay, C.; Nørgaard, K.; Jensen, T.; Parving, H.‐H.; Perrild, H.; Beck‐Nielsen, H.; Christiansen, J. S.; Thorsteinsson, B.; Pedersen‐Bjergaard, U.
Abstract: Aims: To assess the difference between analogue and human insulin with regard to nocturnal glucose profiles and risk of hypoglycaemia in people with recurrent severe hypoglycaemia. Methods: A total of 72 people [46 men, mean ± sd age 54 ± 12 years, mean ± sd HbA1c 65 ± 12 mmol/mol (8.1 ± 1.1%), mean ± sd duration of diabetes 30 ± 14 years], who participated in a 2‐year randomized, crossover trial of basal‐bolus therapy with insulin detemir/insulin aspart or human NPH insulin/human regular insulin (the HypoAna trial) were studied for 2 nights during each treatment. Venous blood was drawn hourly during sleep. Primary endpoints were nocturnal glucose profiles and occurrence of hypoglycaemia (blood glucose ≤ 3.9 mmol/l). Results: During insulin analogue treatment, the mean nocturnal plasma glucose level was significantly higher than during treatment with human insulin (10.6 vs 8.1 mmol/l). The fasting plasma glucose level was similar between the treatments. Nocturnal hypoglycaemia was registered during 41/101 nights (41%) in the human insulin arm and 19/117 nights (16%) in the insulin analogue arm, corresponding to a hazard ratio of 0.26 (95% CI 0.14 to 0.45; P < 0.0001) with insulin analogue. Conclusions: Treatment with insulin analogue reduces the occurrence of nocturnal hypoglycaemia assessed by nocturnal glucose profiles in people with Type 1 diabetes prone to severe hypoglycaemia. Nocturnal glucose profiles provide a more comprehensive assessment of clinical benefit of insulin regimens as compared to conventional recording of hypoglycaemia. What's new?: This trial forms a long‐awaited scientifically based rationale for using insulin analogue to reduce the occurrence of nocturnal hypoglycaemia in people with Type 1 diabetes mellitus and recurrent severe hypoglycaemia. Nocturnal glucose profiles provide a more complete assessment of the clinical significance of nocturnal hypoglycaemia.